INFLUENCE OF AIR PARCELS FROM NORTHERN AND SOUTHERN HEMISPHERES ON RADIOCARBON-BASED INCA CHRONOLOGY - Ancapichun, Santiago; Pawlyta, Jacek; Rakowski, Andrzej Z.; Sieczkowska, Dominika (My University, 2022)
The chronology of Machu Picchu was traditionally associated with the period attributed to the reign of Pachacuti Inca Yupanqui. Within the scheme of the so-called "historical chronology", proposed by John H. Rowe in 1945, the ascension to power of Pachacuti Inca took place around 1438 CE, and the construction of Machu Picchu began by 1450-1460 CE. Several radiocarbon-dated samples may help to understand the chronology of the construction of llaqta of Machu Picchu, Chachabamba, and Choqesuysuy. However, there is a lack of consensus between different radiocarbon-based Inca chronologies because of the lack of information of which calibration curves to use: Northern Hemisphere (NH), Southern Hemisphere (SH), or a mixed calibration curve? Thus, the main goal of the present investigation is to develop a new methodological approach to reconstruct a radiocarbon-based Incan chronology, an approach based on the determination, through modeling, of the proportion of NH and SH air parcels arriving at three relevant Inca settlements. We found air parcel contributions from the NH and SH for Machu Picchu (51% NH and 49% SH), Chamical (29% NH and 71% SH), and Tiquischullpa (41% NH and 59% SH). Thereby, our investigation brings three proportions to mix NH and SH C-14 curves, based on an empirical method and supported by a high-resolution paleoclimatic tracer, for Inca radiocarbon dating studies. Our study emphasizes that great attention should be paid when applying radiocarbon calibration to radiocarbon measurements of samples originating from regions under the influence of the atmospheric circulation-boundary between hemispheres.
Keywords: calibration curves; inca chronology; machu picchu; radiocarbon dating; tlpb